Relation of religious coping with occupational stress and quality of working life for midwives working in maternity hospitals in Zahedan, Iran - Roostaee, Fatemeh; Nikmanesh, Zahra; Sharifi-Rad, Javad; Kiani, Malek; Shahnazi, Ali (International Journal of Research in Medical Sciences, 2016)
Background: The health care center is considered as one of the main sustainable health spheres of human communities, which have direct relationship with human health. It has critical duty of maintaining and restoring health to human society. This study was conducted to investigate the role of religious coping components on occupational stress and quality of midwives' lives. Methods: The study method was descriptive of correlation type and the population consisted of all midwives working in maternity hospitals in Zahedan, in 2014. Three questionnaires were used as data gathering tools including, the quality of working life, occupational stress and religious coping. Data was analyzed using descriptive statistical methods, Pearson correlation coefficient and stepwise regression. Results: Considering the results of Pearson correlation coefficient, there is a significant negative relationship between religious activism (r= -0.454) and occupational stress. Regression analysis also showed that the variability of religious activism explained 45% of variations of occupational stress. In accordance with Pearson correlation test, there is no significant relationship between religious coping components and the quality of life. Conclusions: In conclusion, it is necessary to teach midwives essential trainings to strengthen coping strategies and religious activism in order to reduce occupational stress.